1994
DOI: 10.1063/1.466334
|View full text |Cite
|
Sign up to set email alerts
|

Transient infrared spectroscopy of (η5−C5 H5)Co(CO)2 photoproduct reactions in hydrocarbon solutions

Abstract: Ultrafast photochemistry of CpCo(CO)2 in n-hexane, 1-hexene, and solvent mixtures (298 K) are reported. Multichannel infrared spectra (0.4 ps, 4 cm−1 resolution) identify the vibrational cooling of CpCo(CO)(n-hexane) and CpCo(CO)(1-hexene). The conversion rate of transient n-hexane species to stable 1-hexene product for 0.2–2.0 mol/liter 1-hexene/n-hexane solutions (k=1.4±0.2×1010 M−1 s−1) was determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
64
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(73 citation statements)
references
References 13 publications
9
64
0
Order By: Relevance
“…Whereas it has been found that UV excitation of hexacarbonyls leads to a significant amount of molecules with vibrational hot bands in the CO stretch [4], that has not been observed in a study on dicarbonyls [5]. In the data of our CORM, no distinct hot bands are observed, hence the CO stretch of the photoproduct is not excited in the course of the photolysis.…”
Section: Vibrational Excess Energymentioning
confidence: 47%
See 1 more Smart Citation
“…Whereas it has been found that UV excitation of hexacarbonyls leads to a significant amount of molecules with vibrational hot bands in the CO stretch [4], that has not been observed in a study on dicarbonyls [5]. In the data of our CORM, no distinct hot bands are observed, hence the CO stretch of the photoproduct is not excited in the course of the photolysis.…”
Section: Vibrational Excess Energymentioning
confidence: 47%
“…in [4][5][6]), the photolysis of CO in water-soluble CORMs with suitable properties for biological applications have so far only been studied on a macroscopic scale and at irradiation times of several minutes. For the CORM studied here, UV irradiation eventually leads to the release of two [2] or even all three CO ligands [3].…”
Section: Introductionmentioning
confidence: 99%
“…The 1,3-diene ligand was assumed to retain its s-cis coordination at Os3. This tentative structure of the ns transient was found to correspond well to the fragmentation into {Os 2 (CO) 6 (m-CO)(L) 2 } and {Os(CO) 3 (1,3-diene)} in the presence of L = CO, olefin.…”
Section: Introductionmentioning
confidence: 79%
“…Be-clusters are usually too short-lived to be studied with nanosecond (ns) transient absorption (TA) or TRIR, faster spectroscopic techniques are required in order to characterise the excited states and to monitor the formation of the primary photoproducts. Although several picosecond (ps) TRIR studies of simple, mononuclear transition-metal complexes with, for example, M 0 (Cr, Mo, W [4] or Fe [5] ) and M I (Co, [6] Rh and Ir [7] ) centres have been reported, those of diand polynuclear transition-metal complexes are scarce.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation